IBM Pemberdayaan Kader Antihipertensi di Posyandu Lansia Sumur Gunung - Margiyati Margiyati; Novita Wulansari (Jurnal Pengabdian Masyarakat Waradin, 2024)
Hypertension is one of the main cardiovascular risk factors which is the main cause of death in the world, especially in the elderly. Maximizing the utilization of elderly health posts is one strategy in controlling hypertension in the elderly, but the limited knowledge and skills of elderly health cadres, especially in managing hypertension, make the implementation of elderly health posts less than optimal. Sumur Gunung Elderly Health Post is one of the elderly health posts that routinely runs in Sumurejo Village, but services are still limited to measuring blood pressure, weight, and height, educational services still depend on the health center, there is no exercise, and there are no special provisions for the PMT menu. This is due to the limited knowledge and skills of the cadres. The results of BP examinations on 20 elderly people registered at the Sumur Gunung Elderly Posyandu showed that 35% (7 out of 20 elderly people) had blood pressure > 140/90 mmHg. The questionnaire results showed that 46% of elderly people had not regulated their diet, 75% of elderly people had a habit of drinking coffee, 80% of elderly people had not limited the amount of salt consumed, 50% of elderly people smoked, 60% of elderly people did not know how to treat hypertension. Based on this background, the STIKES Kesdam IV/Diponegoro Community Service Team carried out an activity entitled "IbM Empowerment of Antihypertension Cadres at the Sumur Gunung Elderly Posyandu". The activities included field visits, refreshing cadres, mentoring posyandu, hypertension education, and utilization of cucumber infusion water. The target outputs were to achieve increased knowledge and skills of cadres so that they were empowered in efforts to control hypertension, publication of community service results in national journals, and electronic media. The results of this activity obtained 35% of elderly people were detected to have blood pressure > 140/90 mmHg, there was an increase in knowledge and skills of cadres in implementing elderly posyandu according to standards, and the use of cucumber infused water to reduce hypertension in the elderly.